Mediasi Penal Oleh Kejaksaan Dan Kepolisian Dalam Penanganan Hukum Pencurian Tandan Buah Segar (TBS) Kelapa Sawit Pada Kebun Silau Dunia PT. Perkebunan Nusantara III (Persero) - Parlindungan Silalahi, Juliandi; Mulyadi, Mahmud; Marlina; Lisa Andrianti, Syarifah (UNES Law Review, 2024)
Penal mediation is an alternative that resolves cases, especially the resolution of the crime of theft, which is a minor crime during the investigation process at the Police and Prosecution at the Prosecutor's Office. Supreme Court Circular Letter Number 1691/DJU/SK/PS.00/12/2020 emphasizes the punishment of minor crimes by prioritizing Penal Mediation (restorative justice). The rise of criminal acts of theft, especially in BUMN plantation areas, requires a study of the application of penal mediation in law enforcement in the criminal justice legal system in Indonesia. The formulation of the problem in this research includes how penal mediation is regulated in Indonesian law, the application of Penal Mediation by the police and prosecutors in enforcing Indonesian criminal law, and the burden of penal mediation by the police and prosecutors in the crime of stealing fresh fruit bunches (FFB) at PT Perkebunan Nusantara III (Persero).The research method used is normative juridical research with emphasis on literature review, and supported by a field approach in the form of obtaining additional information from PT. Perkebunan Nusantara III (Persero) Nagori World Glare Gardens, Simalungun Regency. Data collection was carried out using literature studies and field studies. Data analysis was carried out qualitatively.In enforcing the law, the police and prosecutors try to place the law as a means to achieve the goals desired by society, just as the goal of law is that the police and prosecutors try to prioritize justice and expediency rather than legal certaintyThe lack of legal certainty in the application of the principles of penal mediation (restorative justice) considering that there are no legal rules governing the penal mediation process in criminal cases, and law enforcement officials sometimes always adhere to formal legalistic principles so that police officers, namely investigators, ignore the values of justice and benefits in society. The suggestion from this research is that the National Police and Prosecutors need to emphasize the application of progressive law by implementing restorative justice through the discretionary authority of police officers. There needs to be an adjustment in perception between the criminal justice sub-system in implementing the principles of restorative justice with mediation facilities between parties in dispute. There needs to be regulations governing penal mediation as a resolution of criminal cases.